Real-time electromagnetic visualisation using augmented reality and accelerated models - Jalal, Bawar (2023)
Given the recent push towards the next-generation wide band-gap semiconductor devices, electromagnetic interference is a growing concern due to the higher switching frequencies, voltages and currents. Therefore, understanding the electromagnetic behaviour of power electronic systems is important. Visualising the real-time thermal dynamics of these systems is possible using infrared imaging cameras. However, no equivalent tool exists for the real-time prediction of electromagnetic fields.